Sistem Informasi Produk Unggulan Desa Berbasis Web untuk Mendukung Promosi UMKM - Kelvin, M.; Fatoni, Fatoni (TIN: Terapan Informatika Nusantara, 2026)
Banyu Urip Village possesses substantial local economic potential, particularly in the agriculture, fisheries, and home-based microenterprise sectors. However, limited promotional media and the absence of an integrated information system have resulted in low visibility of village flagship products and inefficient manual management of MSME data. This study aims to design and implement a web-based Information System for Featured Village Products as a solution to these challenges. The primary contribution of this research lies in the development of an integrated digital platform that combines MSME data management, digital presentation of featured products, and support for village administrative processes within a single accessible system. The system was developed using the Waterfall method to ensure a structured and systematic development process across all stages. Implementation results indicate that the system significantly improves the dissemination of information to the community, reduces reliance on manual administrative services, and enhances efficiency and transparency in managing village flagship products. Functional testing confirms that all system features operate effectively and meet user requirements. Therefore, this research contributes a practical and replicable model of a web-based village information system that supports local economic development and improves the quality of public services, particularly for rural areas with similar characteristics.